The Fiscal Implications of Climate Change. (Policy Papers; Policy Paper, 2008)
This paper reviews the fiscal implications of climate change, and the potential role of the Fund in addressing them. It stresses that: -- The potential fiscal implications are immediate as well as lasting, and liable to affect-in differing forms and degree-all Fund members. -- Climate change is a global externality problem, calling for some degree of international fiscal cooperation -- ... and has features-an intertemporal mismatch between the (early) costs of action to address climate change and (later) benefits, pervasive uncertainties and irreversibilities (including risk of catastrophe), and sharp asymmetries in the effects on different countries-that raise difficult technical and ethical issues, and hinder policy coordination. -- In addition to itself impacting the public finances, climate change calls for deploying fiscal instruments to mitigate its extent and adapt to its remaining effects.